Changes of intestinal microbiota in the giant salamander (Andrias davidianus) during growth based on high-throughput sequencing - Cai, Mingcheng; Deng, Huan; Sun, Hanchang; Si, Wantong; Li, Xiaoying; Hu, Jing; Huang, Mengjun; Fan, Wenqiao (Frontiers in Microbiology, 2023)
Despite an increasing appreciation of the importance of host–microbe interaction in healthy growth, information on gut microbiota changes of the Chinese giant salamander (Andrias davidianus) during growth is still lacking. Moreover, it is interesting to identify gut microbial structure for further monitoring A. davidianus health. This study explored the composition and functional characteristics of gut bacteria in different growth periods, including tadpole stage (ADT), gills internalization stage (ADG), 1 year age (ADY), 2 year age (ADE), and 3 year age (ADS), using high-throughput sequencing. The results showed that significant differences were observed in microbial community composition and abundance among different growth groups. The diversity and abundance of intestinal flora gradually reduced from larvae to adult stages. Overall, the gut microbial communities were mainly composed of Fusobacteriota, Firmicutes, Bacteroidota, and Proteobacteria. More specifically, the Cetobacterium genus was the most dominant, followed by Lactobacillus and Candidatus Amphibiichlamydia. Interestingly, Candidatus Amphibiichlamydia, a special species related to amphibian diseases, could be a promising indicator for healthy monitoring during A. davidianus growth. These results could be an important reference for future research on the relationship between the host and microbiota and also provide basic data for the artificial feeding of A. davidianus.